2021
DOI: 10.1039/d1ra01858b
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of new lawsone enaminones and theirZ/E(CC)-isomerization induced by organic solvent

Abstract: The synthesis of a new class of lawsone enaminone derivatives by using lawsone, triethyl orthoformate and aromatic amines in the presence of guanidinium chloride under solvent-free conditions has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The E / Z isomerization of β-enaminones is a feasible process because of the push–pull effect. Their energetic barriers have been calculated and experimentally determined by NMR . Considering the protonated species VI and VII , the s-trans isomers have greater stability than the s-cis isomers for 24a / 25a and 27a / 28a (Figure and Table ).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The E / Z isomerization of β-enaminones is a feasible process because of the push–pull effect. Their energetic barriers have been calculated and experimentally determined by NMR . Considering the protonated species VI and VII , the s-trans isomers have greater stability than the s-cis isomers for 24a / 25a and 27a / 28a (Figure and Table ).…”
Section: Resultssupporting
confidence: 83%
“…The selectivity observed is likely controlled by the push–pull effect of the nitrogen lone electron pair of the enamide moiety, which is involved in modifying the tautomeric E / Z -isomerization of the conjugate enaminone system. ,, The Pd­(II)-catalyzed cyclization of the 24a–24c / 25a–25c mixtures in the presence of pivalic acid gave the corresponding tricyclic 9-formyloxazolo­[3,4- a ]­indol-3-ones 26a–26c , albeit in low yields (27–34%). In the absence of pivalic acid, the yields increased modestly (38–46%) (Scheme , in parenthesis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 C NMR analyses of their compounds exhibited chemical shifts for the 1,4-naphthoquinone ring at 181–183 ppm, while the chemical shift of the carbon atom bearing the hydroxyl group of the enol function was close to 160 ppm. In 2021, Olyaei et al 42 reported the synthesis of lawsone enaminone derivatives. They identified two forms and attributed the alkene proton ( 1 H NMR in DMSO) of the enaminone at 9.2 and 9.3 ppm in DMSO.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In 2016, Mohammadpoor‐Baltork and his co‐workers have published synthesis of symmetric and unsymmetric bis‐aminonaphthoquinones from dialdehyde (terephthaladehyde and isophthalaldehyde) and/or diamines (benzene‐1,4‐diamine and 1,2‐ethylenediamine) in the presence of Fe 3 O 4 @TDSN−Bi(III) in EtOH at room temperature [26] . In continuation of our previous works, reported on synthesis of a new series of lawsone derivatives via one‐pot multi‐component reactions, [27–30] herein we reported the synthesis of a new series of bis‐heteroarylaminomethylnaphthoquinones through one‐pot, multi‐component reactions of lawsone, heteroaryl amines and terephthaldehyde in the presence of a catalytic amount of p ‐TSA in CH 3 CN under reflux conditions.…”
Section: Introductionmentioning
confidence: 84%